2024
DOI: 10.52294/001c.118427
|View full text |Cite
|
Sign up to set email alerts
|

MVComp toolbox: MultiVariate Comparisons of brain MRI features accounting for common information across measures

Stefanie A Tremblay,
Zaki Alasmar,
Amir Pirhadi
et al.

Abstract: Introduction Multivariate approaches have recently gained in popularity to address the physiological unspecificity of neuroimaging measures and to better characterize the complexity of biological processes underlying behavior. However, commonly used approaches are biased by the intrinsic associations between variables, or they are computationally expensive and may be more complicated to implement than standard univariate approaches. Here, we propose using the Mahalanobis distance (D2), an individual-level meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…While the metrics derived from DTI, FOD, and NODDI have been unquestionably useful in human neuroscience and often interpreted as specific physiological parameters, there is no clear one-to-one metric-parameter mapping. Further, we and others have shown that there is a high degree of correlation between metrics within and across models (Carter et al, 2022;Figley et al, 2022;Tremblay et al, 2024;Uddin et al, 2019). This suggests that strong conclusions based on theoretical interpretation of a single metric are often difficult to justify.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…While the metrics derived from DTI, FOD, and NODDI have been unquestionably useful in human neuroscience and often interpreted as specific physiological parameters, there is no clear one-to-one metric-parameter mapping. Further, we and others have shown that there is a high degree of correlation between metrics within and across models (Carter et al, 2022;Figley et al, 2022;Tremblay et al, 2024;Uddin et al, 2019). This suggests that strong conclusions based on theoretical interpretation of a single metric are often difficult to justify.…”
Section: Introductionmentioning
confidence: 79%
“…The distance between each subject's microstructural features (i.e., the 10 features) and the average of those features at a given voxel is calculated, resulting in a subject distance vector of the shape 10x1. Then, the distance vector is divided by the covariance between features (in our mvComp approach, this is achieved by multiplication with the pseudoinverse of the covariance matrix; see Tremblay et al, 2024). The same procedure is conducted for each voxel in every subject, resulting in voxelwise D2 maps for each of them.…”
Section: Multivariate Distance Modelmentioning
confidence: 99%
See 3 more Smart Citations